Effect of thermo-mechanical treatment on the current transport properties of Bi(Pb)-Sr-Ca-Cu-O superconductor tapes with nanopowder CoFe2O4 addition - Lau, Kok Tee; Awang Kechik, Mohd Mustafa; Chiu, Wee Siong; Radiman, Shahidan; Abd Shukor, Roslan; Budi, Agus Setyo; Ayof, Mohamad Nizam (American Institute of Physics, 2006)
We study the effect of various thermo‐mechanical treatment on the current transport properties electrical Bi(Pb)‐Sr‐Ca‐Cu‐O tapes with nanopowder CoFe2O4 addition. We found that pinning strength of the tapes without intermediate pressing increases as the sintering temperature increases from 835°C to 855°C, whereas tapes applied with intermediate pressing have lower pinning strength compared with tapes without the pressing. On the contrary, self‐field Jc of tapes without intermediate pressing decreases with increasing sintering temperature. Intermediate pressing are found effective to increase self‐field Jc. The results obtained will be explained with the help of the XRD spectrums and SEM micrographs on the tapes.